A Critical Overview of Interactions of Dithiophosphinates with Base Metal Sulfides and Precious Metals - Napoleon Tercero; D. R. Nagaraj; Raymond Farinato (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"Dialkyl dithiophosphinates are a unique class of collectors used in the flotation processing of Cu- Au, complex polymetallic, and precious metal ores. They are known to exhibit higher selectivity and flotation rates for Cu sulfides, galena, and precious metal values in the presence of other gangue sulfides, than the traditionally used collectors such as dialkyl dithiophosphates and xanthates. They also have an attractive HSE profile. Historically, for most reagents used in flotation, practical methods of chemical usage have preceded detailed scientific understanding of how they work; this applies also to dithiophosphinates. Recently, however, the research community has shown significant interest in this chemistry, and numerous studies have been conducted to understand the fundamentals of interactions of dithiophosphinates with several base metal sulfides and precious metals. A critical overview of fundamental studies, laboratory ore flotation, and plant practice of dithiophosphinates is given in this paper. The findings from these studies are rationalized by drawing on concepts and insights from coordination chemistry. A comparison between the interactions of dithiophosphinates and dithiophosphate analogues with various minerals and metals is also made throughout. We believe that such a critical analysis/overview will be invaluable in identifying gaps in knowledge regarding this important set of compounds, which in turn may provide a basis for the design of studies that can advance understanding of their flotation performance. INTRODUCTIONDialkyl dithiophosphinates are an important member of the class of thiophosphorus compounds that are widely used in flotation beneficiation of base metal sulfide and precious metals ores. Ore flotation studies and plant practice experience have demonstrated their unique properties compared to the traditionally used sulfide collectors such as dialkyl dithiophosphates (their closest analogues) and xanthates. The predominant dialkyl dithiophosphinate used in the industry today is sodium diisobutyl dithiophosphinate (a.k.a. DIBDTPi; AEROPHINE® 3418A1 introduced by American Cyanamid in the late 1970s; Figure 1). The widest application of AEROPHINE 3418A is found in complex polymetallic ores of Cu-Pb-Zn-Ag, Pb-Zn-Ag, and Cu-Zn where it has demonstrated improved recoveries (and flotation rates) of sulfide minerals of Cu, Pb and Ag and selectivity against sphalerite, iron sulfides, and penalty elements (Mingione, 1991). More recently, it has also been used as a collector in the processing of Cu, Cu-Ni, and Ni ores (Guitard et al., 2015) and Cu-Au ores (Dunne, 2005). In general, it is considered to possess the collecting power of xanthates together with the selectivity (against pyrite) of dithiophosphates (Hope et al., 2003a, 2003b), while requiring lower dosages than those reagents (Guitard et al., 2015). AEROPHINE® 3418A has also found an important place in several targeted formulations to improve flotation performance. Other benefits of this reagent include higher flotation rates, having a better HSE (health, safety and environmental) profile2 compared to xanthate, and exhibiting resistance to hydrolysis and oxidation (Guitard et al., 2015). Compared to diisobutyl dithiophosphate (DIBDTP), which is known to contribute significantly to frothing (often leading to over-frothing), AEROPHINE® 3418A is observed to be froth neutral (i.e. it does not alter the existing froth characteristics). As is the case for other flotation reagents, the design and application of AEROPHINE® 3418A has preceded understanding of its behavior at a fundamental level. Recently, there have been numerous fundamental and application studies designed to develop a better understanding of its interaction with sulfide minerals and precious metals. This should help in optimizing its application in flotation and provide a basis to better rationalize its unique selectivity and activity characteristics. Past studies on the interacti"